Understanding the Link Between HIV and Increased Risk of Oropharyngeal Cancer: A Review - Dimas Setyadi Putra; Bachren Azra Saputra (Universitas Muhammadiyah Malang, 2025)
Background: The World Health Organisation (WHO) estimates that the number of people living with HIV will reach 39.9 million by 2023. Although antiretroviral therapy (ART) has increased the life expectancy of people living with HIV (PLHIV), the incidence of cancer has also increased. Objective: This study aims to assess the link between HIV and the risk of oropharyngeal cancer in PLHIV. Methods: The review articles were searched using the keywords ‘oropharyngeal cancer’, ‘people living with HIV’, and ‘PLWHA’ with the combination of ‘OR’ and ‘AND’ using the Scopus database. Results: According to the nineteen articles found in the initial search, only five articles with populations in the United States, Spain, Korea, and France met the inclusion criteria. This study found that HIV increases the risk of oropharyngeal cancer. In addition, exposure to ART showed protection against oral human papillomavirus (HPV) infection, which may reduce the risk of cancer. Conclusions: HIV increases the risk of oropharyngeal cancer. Thus, ensuring adherence to ART might serve as a protective agent against HPV and reduce the risk of cancer progression in PLHIV.